Application of Linear Prediction Technique to Passive Synthetic Aperture Processing. (24th March 2010) - Hou Hou, Yunshan Yunshan; Huang Huang, Jianguo Jianguo; Jiang Jiang, Min Min; Jin Jin, Yong Yong
Abstract : A method for the synthesis of an aperture with improved angular resolution and array gain is described. The proposed method explores the merit of linear prediction technique to improve the performance of conventional ETAM (extended towed array measurements) method. Previous efforts to improve the ETAM method generally focused on how to get more accurate estimation of overlap correlator, with an aim to reduce bearing estimation variance. In this paper, however, we discuss how to further improve the angular resolution when the effective synthetic aperture is rather limited. We resort to linear prediction technique to further extend the synthetic aperture obtained by ETAM, which produces a much longer virtual aperture. Results from simulations and lake experiment showed that the proposed LP-ETAM method achieved better angular resolution than ETAM.